2018
DOI: 10.1111/den.13305
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic‐ultrasound‐guided coil and cyanoacrylate embolization for gastric varices and the roles of endoscopic Doppler and endosonographic varicealography in vascular targeting

Abstract: Objective To report the results of endoscopic ultrasound‐guided injection of coils with cyanoacrylate (CYA) using a less‐expensive coil with an emphasis on the roles of Doppler and endosonographic varicealography (EV) in identifying the feeder vessel in gastric varix treatment. Methods An observational, descriptive study with prospectively collected data. Patients with gastric varices (GV) were included and were treated by endoscopic ultrasound‐guided injection of CYA and a less‐expensive coil. Technical succe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 29 publications
1
29
0
4
Order By: Relevance
“…From our findings, when cyanoacrylate is combined with endoscopic ultrasound guided coils to treat gastric varices the pooled risk of rebleeding is 0.07(confidence interval: 0.03-0.11). This finding is more or less similar to that reported by Bhat et al (2016) [43] but is higher than that reported by Robles-Medranda et al (2019) [44]. The reason for the differences could be explained by different sample sizes among studies pooled.…”
Section: Discussionsupporting
confidence: 85%
“…From our findings, when cyanoacrylate is combined with endoscopic ultrasound guided coils to treat gastric varices the pooled risk of rebleeding is 0.07(confidence interval: 0.03-0.11). This finding is more or less similar to that reported by Bhat et al (2016) [43] but is higher than that reported by Robles-Medranda et al (2019) [44]. The reason for the differences could be explained by different sample sizes among studies pooled.…”
Section: Discussionsupporting
confidence: 85%
“…Historically, endoscopic therapy for GV has relied on intravenous injection of acrylate polymers often used in conjunction with lipiodol, a radio-opaque ionized oil which slows polymerization of these polymers allowing more time for injection [19]. Cyanoacrylate injection has been associated with multiple complications [8][9][10][11][12], most notably systemic embolization (e. g. pulmonary embolism) in up to 2 % to 3 % of cases, and sclerosant or glue extrusion which can occur within 1 to 3 months and can lead to recurrent variceal bleeding [19][20][21]. Other complications include fevers, sepsis, and gastric ulcer formation.…”
Section: Discussionmentioning
confidence: 99%
“…associated with complications, such as systemic embolization, failed withdrawal of needle from variceal nest after injection and deep ulceration resulting in re-bleeding [8][9][10][11]. To mitigate against these complications, cyanoacrylate has been used as adjunctive therapy following hemostatic coils delivered intravascularly under endoscopic ultrasound (EUS) guidance [12,13]. Theoretically coils provide scaffolding for localized glue polymerization, however adverse events including rebleeding and embolization are still seen with combination therapy [13,14].…”
Section: Conclusion Eus-guided Coil Embolization In Combinationmentioning
confidence: 99%
“…Combination of coils and CYA glue in the afferent portion of the perforator has reported complete variceal obliteration in 96.6% of cases with 100% technical success rate and immediate disappearance of GV in 80% of patients in a recent study. 13 A recent systemic review and meta-analysis 14 showed that EUS-guided angiotherapy is safe and effective procedure with high technical success rate.…”
Section: Discussionmentioning
confidence: 99%